The Effectiveness of Group Guidance Using the Scaling Technique in Improving Students’ Academic Self-Concept - Ismaniar Hasanah Sagala; Nurussakinah Daulay (Universitas Negeri Semarang, 2025)
Background - Based on the researcher’s observations at the Jabal Rahmah Mulia Plus Junior High School Boarding School, it was found that students exhibited a low level of academic self-concept. A low academic self-concept may cause students to become easily discouraged, lose their motivation to learn, and be reluctant to participate actively in class because they perceive themselves as less intelligent than their peers. Academic self-concept refers to an individual’s perception, evaluation, and belief in their own abilities within the academic domain. Purpose - This study aims to determine whether group guidance using the scaling technique is effective in improving students’ academic self-concept. Method/approach - This study employed a quantitative approach with a quasi-experimental design using a one-group pretest–posttest model. The participants consisted of eight students with low levels of academic self-concept, selected through purposive sampling. The research instrument used in this study was an academic self-concept questionnaire. Findings - The results of this study indicate that group guidance services using the scaling technique are effective in improving students’ academic self-concept. Data were analyzed using the Wilcoxon Signed Ranks Test, which yielded a Z value of -2.527 with a p-value of 0.012. Since the p-value < 0.05, it can be concluded that there is a significant difference between the pre-test and post-test scores. Conclusions - Group guidance services using the scaling technique can be utilized as a form of intervention to enhance students’ academic self-concept. This study is also expected to serve as a reference for the implementation of guidance and counseling services in schools, particularly in addressing psychological issues related to students’ academic aspects. Novelty/Originality/Value - This study offers novelty by emphasizing the effectiveness of group guidance using the scaling question technique in improving academic self-concept. It provides a theoretical contribution by expanding the understanding of the impact of the scaling question technique on students’ cognitive–reflective aspects, as well as a practical contribution by offering an alternative group guidance strategy for school counselors to optimize students’ academic potential.